The Root Hair Development of Pectin Polygalacturonase PGX2 Activation Tagging Line in Response to Phosphate Deficiency - Zhang, Qing; Deng, Aiwen; Xiang, Min; Lan, Qiuyan; Li, Xiaokun; Yuan, Shuai; Gou, Xin; Hao, Shuang; Du, Juan; Xiao, Chaowen (Frontiers in Plant Science, 2022)
Pectin, cellulose, and hemicellulose constitute the primary cell wall in eudicots and function in multiple developmental processes in plants. Root hairs are outgrowths of specialized epidermal cells that absorb water and nutrients from the soil. Cell wall architecture influences root hair development, but how cell wall remodeling might enable enhanced root hair formation in response to phosphate (P) deficiency remains relatively unclear. Here, we found that POLYGALACTURONASE INVOLVED IN EXPANSION 2 (PGX2) functions in conditional root hair development. Under low P conditions, a PGX2 activation tagged line (PGX2AT) displays bubble-like root hairs and abnormal callose deposition and superoxide accumulation in roots. We found that the polar localization and trafficking of PIN2 is altered in PGX2AT roots in response to P deficiency. We also found that actin filaments were less compact but more stable in PGX2AT root hair cells, and that actin filament skewness in PGX2AT root hairs was recovered by treatment with 1-N-naphthylphthalamic acid (NPA), an auxin transport inhibitor. These results demonstrate that activation tagging of PGX2 affects cell wall remodeling, auxin signaling, and actin microfilament orientation, which may cooperatively regulate root hair development in response to P starvation.